A novel NAA10 p.(R83H) variant with impaired acetyltransferase activity identified in two boys with ID and microcephaly - Rasmus Ree; Anni Sofie Geithus; Pernille Mathiesen Tørring; Kristina Pilekær Sørensen; Mads Damkjær; DDD study; Sally Ann Lynch; Thomas Arnesen (BMC, 2019)
Abstract Background N-terminal acetylation is a common protein modification in human cells and is catalysed by N-terminal acetyltransferases (NATs), mostly cotranslationally. The NAA10-NAA15 (NatA) protein complex is the major NAT, responsible for acetylating ~ 40% of human proteins. Recently, NAA10 germline variants were found in patients with the X-linked lethal Ogden syndrome, and in other familial or de novo cases with variable degrees of developmental delay, intellectual disability (ID) and cardiac anomalies. Methods Here we report a novel NAA10 (NM_003491.3) c.248G > A, p.(R83H) missense variant in NAA10 which was detected by whole exome sequencing in two unrelated boys with intellectual disability, developmental delay, ADHD like behaviour, very limited speech and cardiac abnormalities. We employ in vitro acetylation assays to functionally test the impact of this variant on NAA10 enzyme activity. Results Functional characterization of NAA10-R83H by in vitro acetylation assays revealed a reduced enzymatic activity of monomeric NAA10-R83H. This variant is modelled to have an altered charge density in the acetyl-coenzyme A (Ac-CoA) binding region of NAA10. Conclusions We show that NAA10-R83H has a reduced monomeric catalytic activity, likely due to impaired enzyme-Ac-CoA binding. Our data support a model where reduced NAA10 and/or NatA activity cause the phenotypes observed in the two patients.